Findings before diagnoses of asthma among the elderly in a longitudinal study of a general population sample - Burrows, Benjamin; Lebowitz, Michael D.; Barbee, Robert A.; Cline, Martha G. (Journal of allergy and clinical immunology, 1991)
Forty elderly subjects who denied ever having asthma or emphysema on enrollment in a longitudinal epidemiologic study later reported consulting a doctor for asthma when they were older than 60 years of age. The average age at which the diagnosis was reported was 70.8 years, after a mean follow-up of 8.5 years. Findings on enrollment in the newly diagnosed subjects with asthma are compared with findings in the 1145 subjects who provided follow-up information when they were older than age 60 years but had never developed asthma. At the time of enrollment, most subjects later diagnosed as having asthma already had wheezing symptoms, suggesting at least a mild asthmatic state, and many subjects had impaired ventilatory function, a positive allergy skin test (especially in association with rhinitis), and blood eosinophilia. Thirty-five percent of the subjects recalled “respiratory trouble before age 16” despite denying prior asthma. The likelihood of a new asthma label was very closely related to the age-sex-standardized serum-IgE level before diagnosis. Newly diagnosed subjects with asthma demonstrated much greater rates of decline in FEV 1 than control subjects or than subjects who already had known asthma on enrollment. We conclude that (1) symptoms suggesting asthma are usually present for many years before the diagnosis of the disease in elderly subjects, (2) the serum-IgE level is closely related to the likelihood of a subsequent asthma diagnosis, even in this age group, and (3) a rapid fall in lung function often occurs around the time of initial diagnosis.